L’exposé de la réprobation dans l’Ihyā’ d’al-Ghazālī: quelques observations concernant l’influence d’al-Muhāsibī (Doctor Virtualis, 2022)
In the second part of the Book of the Condemnation of Status and Ostentation – the twentieth-eight book of his major work, The Revival of the Religious Sciences – al-Ghazālī draws much inspiration from al-Muhāsibī, above all from his work al-Ri’āya al-huqūq Allāh (Eyeservice to God’s Laws). The very fact that al-Ghazālī explicitly mentions al-Muhāsibī’s name no less than four times throughout this section clearly testifies to his profound admiration for this great early mystic. A close examination of these references and their context reveals a great familiarity with and an extensive use of the Ri’āya, as well as a direct access to another major work of al-Muhāsibī, i.e., Kitāb al-Wasāya (The Book of Commandments). Moreover, al-Ghazālī’s choice of specific Qur’anic verses and of Traditions, both prophetic and stories, is much indebted to the Ri’āya, as becomes clear on the basis of an examination of the first chapter of this second part which consisting entirely of quotations of Qur’anic verses and Traditions concerning the issue of ostentation. As to the second chapter, which focuses on the ways used to draw people’s attention to oneself both in religious as well as in wordly acts, it shares many features with al-Muhāsibī’s exposition in the Ri’āya, including the almost verbatim copying of some passages. Finally, al-Ghazālī’s use of the Ri’āya in each of the other chapters is briefly indicated. This study shows that al-Muhāsibī was not just a major source for al-Ghazālī – a fact already known for nearly a century – but the major source, at least for this section of his Revival. However, at the same time, this study makes clear that al-Ghazālī is not guilty of blind plagiarism.
Keywords: al-Ghazālī; al-Muhāsibī; Ri’āya al-huqūq Allāh; fiqh (islamic law)